К вопросу о названии и дате учреждения византийской фемы в Таврике - Науменко, В.Е. (Материалы по археологии, истории и этнографии Таврии, 1998)
The author examines the problems connected with the original history of Byzantine thema in Taurica. Critical reading of the known written sources on this problem enables us to make more precise the date of establishing thema in the Crimea and date this event back to the spring-summer of 841. At first in Byzantine sources the Crimean thema was known as ‘’Klimata”. The analysis of the data in historic and hagiographie works, official church documents, sphragistic material shows that in the sources of the 9th-10th centuries this term meant the regions of Taurica, which were a part of the Byzantine empire or which were under her political and cultural influence. In territory they were bounded by the fortresses Cherson in the west and Bosporos in the east. In more specific aspect ‘’Klimata” are administrative units, into which the territory of Taurica was divided. Hence, it is in order that this name of a newly established thema on the territory of Taurica is used.